PELATIHAN PEMBUATAN SABUN CAIR UNTUK PENCEGAHAN PENULARAN COVID-19 DI KELURAHAN TIGA BALATA - Apriani Sijabat; Osco P Sijabat (LPPM Universitas Flores, 2021)
The Covid-19 pandemic is still sweeping the entire world, therefore understanding and information is needed regarding the prevention of covid-19 transmission. One of them is by washing your hands using running water and soap. The purpose of this activity is to provide socialization to the community in the Tiga Balata village to prevent the spread of Covid-19. Activities carried out by providing training in making liquid hand washing soap. It is hoped that from this activity the people of Tiga Balata Village will become an example to socialize ways to prevent the spread of Covid-19 to the surrounding community. This activity is also expected to be able to create business opportunities for the community in the midst of the Covid-19 pandemic. The method used in this service is the method of counseling and training. This hand washing soap-making training aims to improve community skills, especially participants in activities amid the Covid-19 pandemic. The result of this service is that the community is enthusiastic about participating in the training and has produced liquid soap products for personal use and commercial use as business opportunities.